2017
DOI: 10.1136/postgradmedj-2016-134630
|View full text |Cite
|
Sign up to set email alerts
|

Cost minimisation analysis of thermometry in two different hospital systems

Abstract: Sensitivity analyses showed that the price of current consumables had the highest impact on the model in both hospital settings, with TAT up to 10 times cheaper in that regard over TMT at UHCZ, potentially leading to considerable budget savings within a year of hospital-wide implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Oral thermometry is also contraindicated in unconscious and delirious patients 18,21 . In addition, because probe covers and frequent alcohol swabs are crucial for reducing cross-infection when using oral thermometers, these consumables can add to clinic costs and also add workload to already overwhelmed staff in outbreak-prone areas 4,15,21 . Tympanic infrared thermometers are noninvasive, inexpensive, quick and need no consumables.…”
Section: Non-invasive Thermometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Oral thermometry is also contraindicated in unconscious and delirious patients 18,21 . In addition, because probe covers and frequent alcohol swabs are crucial for reducing cross-infection when using oral thermometers, these consumables can add to clinic costs and also add workload to already overwhelmed staff in outbreak-prone areas 4,15,21 . Tympanic infrared thermometers are noninvasive, inexpensive, quick and need no consumables.…”
Section: Non-invasive Thermometrymentioning
confidence: 99%
“…TAT has many clinical benefits including the fact that it poses minimal risk of infection, limited risk of injury (i.e. perforation/ discomfort), and it allows for an easily accessible BTM that meets with little patient resistance 1,15,24,25 . Further, many studies comparing the utility and accuracy of TAT in comparison to rectal and oral thermometry, showed that TAT can result in time-savings for clinicians who work with pediatric populations 12 , but that TAT also tends to underperform 1,3,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Oral thermometry is also contraindicated in unconscious and delirious patients ( Lawson et al, 2007 ; Pappas, 2012 ). In addition, because probe covers and frequent alcohol swabs are essential for reducing cross-infection when using oral thermometers, these consumables can add to clinic costs and also add workload to already overwhelmed staff in outbreak-prone areas ( Pappas, 2012 ; Barringer et al, 2011 ; Hayes et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Postgraduate Medical Journal contains an interesting and important publication on thermometry-related expenditure for hospital patients in two different parts of the world 1. As explained by the authors, the monitoring of body temperature is an essential feature of clinical practice in hospitals.…”
mentioning
confidence: 99%
“…The study by Hayes et al 1 actually entailed two CMAs, both from the perspective of the healthcare provider and stemmed from accepting that all the prevailing forms of thermometry have more or less equally acceptable accuracy, reliability and safety. This premise was backed up by sources cited by the authors and by others 4–7.…”
mentioning
confidence: 99%